Optimization Design Method of Decoupling Capacitor in PCB Hardware of Electric Vehicle Controller. (May 2017) - Li, Guangzhao; Zhai, Li; Feng, Huiyuan; Gu, Hongtao
Abstract: This paper proposes an optimization design method of decoupling capacitor based on geometric average of resonance points. Impedance characteristics of each 5 V port have been analyzed (100kHz-1GHz). In order to meet the needs of the target impedance, a method of decoupling capacitor chosen upon average of resonant points is used for the port which are beyond the target impedance. To verify the decoupling performance of decoupling capacitors, an example case of the chip DCP010505BP was investigated, and after six decoupling capacitors, the impedance of the chip DCP010505BP is maintained below the target impedance throughout the frequency range of interest.